1983
DOI: 10.1104/pp.72.1.194
|View full text |Cite
|
Sign up to set email alerts
|

Extraction and Partial Characterization of the Glycine Decarboxylase Multienzyme Complex from Pea Leaf Mitochondria

Abstract: Glycine decarboxylse has bee sic solubUized from pea (Piwm sadvun) leaf ntochd as an oe wder. he enzyme was dependent on added ditldotdreltol and pyridoxal phpte for maxima activit. The enzyme preparation could catbyze the exchagte of CO2 Ito the carboxyl carbon of glycine, the reverse of the glycine decarboxylase reati by converting serine, NH1,, and CO into glycine, and 14C02release from 11-_4CIglyclne. The half-maximal concentrations for the glycIne-bcarbonate exchage reaction were 1.7 mIma glyclne, 16 mfll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
1

Year Published

1984
1984
1991
1991

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(21 citation statements)
references
References 20 publications
2
18
1
Order By: Relevance
“…The results described above help explain one of the early anomalies noted with the glycine decarboxylase complex, the nonlinear response of the enzyme activity to increasing enzyme concentrations (14,18). At low enzyme concentrations (less than 50 Ag crude matrix extract/mL or about 33 nM Hprotein) the amount of activity was disproportionately low when compared to the rates measured at higher enzyme concentrations.…”
Section: Role Of the H-protein In The Complexmentioning
confidence: 79%
See 1 more Smart Citation
“…The results described above help explain one of the early anomalies noted with the glycine decarboxylase complex, the nonlinear response of the enzyme activity to increasing enzyme concentrations (14,18). At low enzyme concentrations (less than 50 Ag crude matrix extract/mL or about 33 nM Hprotein) the amount of activity was disproportionately low when compared to the rates measured at higher enzyme concentrations.…”
Section: Role Of the H-protein In The Complexmentioning
confidence: 79%
“…H-protein activity was assayed by the method of Motokawa and Kikuchi (13,20 (18,19). Figure 1 shows the fractionation ofthe purified component enzymes and the concentrated matrix enzymes on identical sucrose density gradients.…”
Section: Methodsmentioning
confidence: 99%
“…The four subunits of GDC have been isolated and characterized in detail from both plant and animal sources (2,7,8,10,19,23). Of the four proteins, the L protein, lipoamide dehydrogenase, is the only one known to be involved in other enzyme reactions, notably the a-keto acid dehydrogenase complexes, PDH, and 2-oxoglutarate dehydrogenase.…”
Section: Discussionmentioning
confidence: 99%
“…INH, however, has limited usefulness because of the high concentrations (13) long incubation periods needed for inhibition. Cyanide has also been shown to inhibit glycine decarboxylase, probably by reacting with PLP (2,11), but this compound is pleiotropic in its effects. Glycine hydroxamate and aminoacetonitrile are structurally related to glycine and have been shown to inhibit glycine oxidation by cells (or leaf discs) and isolated mitochondria (6,16).…”
mentioning
confidence: 99%
“…Glycine hydroxamate and aminoacetonitrile are structurally related to glycine and have been shown to inhibit glycine oxidation by cells (or leaf discs) and isolated mitochondria (6,16). Because of the relative insensitivity of the isolated enzyme to aminoacetonitrile (11,18), it was suggested that this compound may not inhibit the glycine decarboxylase complex directly. Arsenite inhibits a wide range of thiol containing enzyme including the lipoamide-based complexes, pyruvate dehydrogenase and a-ketoglutarate dehydrogenase, and has been shown to inhibit isolated glycine decarboxylase (11) as well as glycine oxidation by mitochondria (17).…”
mentioning
confidence: 99%